INDONESIAN VERSION OF THE PAINDETECT QUESTIONNAIRE IN THE ASSESSMENT OF NEUROPATHIC PAIN: A VALIDITY AND RELIABILITY STUDY - Karolina Margareta; Manfaluthy Hakim; Mohammad Kurniawan; Tiara Anindhita; Herqutanto (Jurnal Sinaps, 2021)
Objective: To develop an Indonesian version of PainDETECT Questionnaire (PDQ-Ina) and assess itsvalidity and reliability. Methode: The validity and reliability study was conducted at the Neurology ClinicCipto Mangunkusumo General Hospital, Jakarta from March 2014 until May 2014 using cross sectionaldesign. Sample of the research was done by non random consecutive sampling method. and were takenfrom each participant who met the inclusion criteria, measuring reliability of painDETECT Questionnaires(PDQ) using statistical analysis and retest test method within 24-48 hours interval. Result:There were150 subjects with chronic pain. Divided in to 3 types of group based on Indonesian version PDQ scoring,75 patients having nociceptive pain, 42 were mixed pain and 33 patients having neuropathic pain. Withinvalidation criteria analysis there were high correlation between PDQ-Ina with LANSS instrument as goldstandard (r= 0,082,p<0,001), AUC 85,5%, sensitivity 78,3% and specificity 78,7% with the optimal cut offpoint ≥17. The reliability of internal consistency Cronbach’s Alpha value were 0,710 and the test retestrealibility were 0,96. Conclusion :The Indonesian version of the PDQ is a valid and reliable scale andhave a good sensitivity and specificity to be used to determine neuropathic component of chronic pain.